Estimated Effective Dose Out of Fields in LINAC Radiotherapy Variant iX in Cervical Cancer - Kadek Listuayu; Johan Noor; Bunawas Bunawas (Natural B, Journal of Health and Environmental Sciences, 2016)
Linac operated at energies above 8 MV can result in photoneutron emissions arising from the interaction between high-energy photons striking the constituent materials such as collimator, the target and the scattering foil. This secondary radiation may increase the risk of secondary cancers and additional radiation dose received in addition to dose of photons. This study estimates the dose out of the field around cervix cancer in the form of an effective dose of neutron and photon. Measurements were carried out using termoluminescence (TLD) detector pairs, TLD 600 and TLD TLD 700. Neutron dose distribution was determined by placing the TLD pairs at 8 points scattered in the phantom.. Linac irradiations at a dose of 2 Gy were conducted three times that produced effective dose neutron range from 0.3 mSv to 4.8 mSv. While the effective dose photon as read by the TLDs range from 42.9 to 920.1 mSv.The effective dose of neutron and photon received were less for points located further away from the point of isocentre.